Book Reviews - Sarkar, Dhrubajyoti; Mandal, Sagar Taranga (Multicultural Shakespeare: Translation, Appropriation and Performance, 2013)
Shakespeare and Asia. Shakespeare Yearbook vol. 17, Eds. Yang Lingui, Douglas A. Brooks, Ashley Brinkman, New York: The Edward Mellen Press, 2010. Pp. Vii+528. ISBN-13: 978-0-7734-3726-5, ISBN-10: 0-7734- 3726-6 Abdulla Al-Dabbagh, Shakespeare, the Orient, and the Critics, New York and Oxford: Peter Lang, 2010. Pp. Ix + 148. ISBN978-1-4331-1059-7